2007
DOI: 10.1111/j.1348-0421.2007.tb03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Application of AvaII PCR Restriction Fragment Length Polymorphism Analysis (AvaII PRA) Targeting 644 bp Heat Shock Protein 65 (hsp65) Gene to Sputum Samples

Abstract: Of the validated species in the genus Mycobacterium, M. tuberculosis is the most common and important pathogen and causes 2 million deaths and over 8 million cases of tuberculosis annually worldwide (2-4, 7). In addition to the multidrug resistant strains of M. tuberculosis, NTM (non-tuberculosis mycobacteria) infection can cause other serious clinical problems. Moreover, because the drugs of choice for the treatment of NTM infection are heavily dependent on taxonomic statuses (15,19,20), it is of importance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Molecular markers have been used to elucidate the taxonomy of the Mycobacterium of P. nobilis. Although the hsp65 gene has been reported to be the most suitable target for the differentiation of mycobacteria species (Kim et al, 2005b;Mun et al, 2007), it has also been reported that some discrepancies can exist between hsp65, internal transcribed spacer 1 (ITS1) and 16S rDNA results for species differentiation. When comparing the hsp65 and ITS, we noticed that the 16S-23S internal transcribed spacer region (ITS) had better identification ability.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers have been used to elucidate the taxonomy of the Mycobacterium of P. nobilis. Although the hsp65 gene has been reported to be the most suitable target for the differentiation of mycobacteria species (Kim et al, 2005b;Mun et al, 2007), it has also been reported that some discrepancies can exist between hsp65, internal transcribed spacer 1 (ITS1) and 16S rDNA results for species differentiation. When comparing the hsp65 and ITS, we noticed that the 16S-23S internal transcribed spacer region (ITS) had better identification ability.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the above hypothesis, a phylogenetic analysis of the three M. yongonense strains was performed using two other genes (16S rRNA and hsp65 genes), which have been used widely for mycobacteria taxonomies and diagnostics [13], [19], [20], [21]. Despite some problems in the bacteria taxonomy, the 16S rRNA gene sequence-based comparisons have been and remain invaluable in describing the prokaryotic diversity; they are indispensable in the delineation of bacterial species [22].…”
Section: Resultsmentioning
confidence: 99%
“…PCR–RFLP is a traditional method to detect gene polymorphisms (Mun et al 2007 ; Wardak et al 2005 ). The advantage of this method is simple, fast and effective, and many restriction enzymes are cheap and commercially available.…”
Section: Introductionmentioning
confidence: 99%